Depression, anxiety and stress due to COVID -19 in educational actors - Aldana Zavala, Julio Juvenal (2021)
Family members are exposed to a double stress; the first related to the factors which normally affect all people living through this period of pandemic; and the second, the stress resulting from the tension generated by the danger of contagion. In this context, the aim of this study was to analyze depression, anxiety and stress in the family members of medical personnel who treat patients with COVID-19 at the Villa El Salvador Emergency Hospital in Lima, Peru. The method employed was descriptive, with a non-experimental observational design, applied to 325 fa-mily members of the medical staff who care for COVID-19 patients at the Villa El Salvador Emergency Hospital, in the province of Lima, Peru. It was found that the categories of severe stress and extremely severe stress were present in 64% of the individuals studied. It was therefore concluded that, as a result of the lockdown in response to COVID-19, a combination of predictors of anxiety, depression and stress is generated.